2016
DOI: 10.1158/1535-7163.mct-15-0709
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Inhibits Glioma Growth by Regulating miRNA-199b-5p–HES1–AKT Pathway

Abstract: Tigecycline is a broad-spectrum, first-in-class glycylcycline antibiotic currently used to treat complicated skin infections and community-acquired pneumonia. However, there is accumulating evidence showing that tigecycline has anticancer properties. In this study, we found tigecycline could inhibit cell proliferation by inducing cell-cycle arrest, but not apoptosis in glioma. To find the underlying mechanism of how tigecycline inhibits cell proliferation, the expression of miRNAs, which were related to regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…As it has been reported that tigecycline impairs the cell viability mainly through inducing cell cycle arrest rather than apoptosis, we first analysed the effect of tigecycline on the cell cycle of MM cells and found that tigecycline treatment led to an increase in G0/G1 phase with diminished S phase (Figure A), suggesting that tigecycline is capable of inducing G0/G1 arrest to decelerate the cell cycle, and preventing the cells from entering the S phase and proliferating. As CDK2 is one of the key kinases controlling G1/S transition and DNA replication and p21 is a critical regulator of CDK2, we measured these two proteins and found that tigecycline markedly decreased the levels of CDK2 and p21 in three MM cell lines RPMI‐8226, NCI‐H929, and U266 (Figure B).…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…As it has been reported that tigecycline impairs the cell viability mainly through inducing cell cycle arrest rather than apoptosis, we first analysed the effect of tigecycline on the cell cycle of MM cells and found that tigecycline treatment led to an increase in G0/G1 phase with diminished S phase (Figure A), suggesting that tigecycline is capable of inducing G0/G1 arrest to decelerate the cell cycle, and preventing the cells from entering the S phase and proliferating. As CDK2 is one of the key kinases controlling G1/S transition and DNA replication and p21 is a critical regulator of CDK2, we measured these two proteins and found that tigecycline markedly decreased the levels of CDK2 and p21 in three MM cell lines RPMI‐8226, NCI‐H929, and U266 (Figure B).…”
Section: Resultssupporting
confidence: 56%
“…As it has been reported that tigecycline impairs the cell viability mainly through inducing cell cycle arrest rather than apoptosis, 11 we first analysed the effect of tigecycline on the cell cycle of MM cells and found that tigecycline treatment led to an increase in G0/G1 phase with diminished S phase (Figure 2A), suggesting that tigecycline is capable of inducing G0/G1 arrest to decelerate the cell cycle, and preventing the cells from entering the S phase and proliferating.…”
Section: Tigecycline Induces Cell Cycle Arrest At G0/g1 Phase In MMmentioning
confidence: 99%
See 2 more Smart Citations
“…Further study demonstrated that after treating glioma U87 and U128 cells with TIG, the miRNA-199b-5p level obviously increased and the level of HES family BHLH transcription factor 1 (HES1), a target of miRNA-199b-5p, obviously decreased. Moreover, TIG decreased Akt phosphorylation at Ser473 and increased its target p21 level via the miRNA-199b-5p-HES1 axis (Yang et al, 2016). Another study showed that TIG could induce cell G1/S phase arrest and suppress migration/invasion by down-regulating the level of p21 in melanoma A375 and MV3 cell lines (Hu et al, 2016).…”
Section: Akt Signaling As a Target Of Tigmentioning
confidence: 99%